The Influence of Return on Assets, Return on Investment, Debt to Equity Ratio, and Dividend Payout Ratio on Firm Value (An Empirical Study on the Banking Sector Listed on the Indonesia Stock Exchange) - Nur Ayu, Luh Nyoman Fajar; Suci, Ni Made; Suarmanayasa, I Nengah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine and analyze the influence of Return on Assets (ROA), Return on Investment (ROI), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) on firm value in the banking sector listed on the Indonesia Stock Exchange during the 2021–2023 period. This research employs a quantitative causal approach to test the impact of ROA, ROI, DER, and DPR on firm value in the banking sector. The sample was determined using purposive sampling, consisting of 11 banking companies that consistently distributed dividends throughout the 2021–2023 period, resulting in a total of 33 observational data points. Secondary data in the form of financial statements were obtained from the official websites www.idx.co.id and each respective company. The analysis technique used was multiple linear regression, along with classical assumption testing and data processing using SPSS version 26. The results of the study indicate that Return on Assets (ROA), Return on Investment (ROI), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) have a significant influence on the firm value of banking companies listed on the Indonesia Stock Exchange during the 2021–2023 period, both partially and simultaneously. This indicates that asset utilization efficiency, investment optimization, capital structure management, and consistent dividend policies are crucial factors influencing investor perceptions of firm value, and they serve as a basis for investment decision-making and corporate managerial strategies.